2012
DOI: 10.1161/hypertensionaha.112.193607
|View full text |Cite
|
Sign up to set email alerts
|

Renal Responses to Chronic Suppression of Central Sympathetic Outflow

Abstract: Chronic electrical activation of the carotid baroreflex produces sustained reductions in sympathetic activity and arterial pressure and is currently being evaluated as hypertension therapy for patients with resistant hypertension. However, the chronic changes in renal function associated with natural suppression of sympathetic activity are largely unknown. In normotensive dogs we investigated the integrative cardiovascular effects of chronic baroreflex activation (2 weeks) alone and in combination with the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Iliescu 24 found that baroreflex activation combined with amlodipine resulted in an even greater BP decrease but no change in GFR compared with only baroreflex activation. Our results do not entirely support this observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iliescu 24 found that baroreflex activation combined with amlodipine resulted in an even greater BP decrease but no change in GFR compared with only baroreflex activation. Our results do not entirely support this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Iliescu 24 investigated the renal responses to baroreflex activation (for 2 weeks) in 6 normotensive dogs and found, along with a substantial BP reduction, about 10% and 20% decrease in GFR and renal blood flow, respectively, and no change in renal vascular resistance during the activation period. Lohmeier and Iliescu 23,24 explained the decrease in GFR by attenuation of tubular sodium reabsorption attributable to suppression of renal sympathetic nerve activity. This leads to increased sodium chloride delivery to the macula densa, which is expected to result in constriction of afferent arteriole by tubuloglomerular feedback and a concomitant GFR reduction.…”
Section: Discussionmentioning
confidence: 99%
“…28 Chronic baroreflex activation alone decreased blood pressure, plasma renin activity, and glomerular filtration rate. Amlodipine alone decreased blood pressure and increased plasma renin activity, but glomerular filtration rate was unchanged.…”
Section: Carotid Baroreflex Activationmentioning
confidence: 99%
“…First, Thrasher 15 produced chronic unloading of arterial baroreceptors in dogs, in which 1 carotid sinus and the aortic depressor nerve were cut, and the carotid sinus from the remaining innervated region was isolated from the systemic arterial pressure. Baroreceptor unloading was then induced by ligating the common carotid artery proximal to the innervated sinus, which led to an increase in arterial pressure that lasted for several weeks; although the initial increase in arterial pressure was not sustained, the level remained above control levels.15 Lohmeier et al 12,13 subsequently observed that electric stimulation of the carotid baroreceptors for 7 days and 2 weeks elicits a sustained reduction in arterial pressure and heart rate associated with a decrease in plasma norepinephrine and renin although the effect may be model dependent and renal nerve independent. In addition to these important observations, a growing body of evidence from recent studies suggests that activation of the sympathetic nervous system has an important role in both the occurrence and the progression of hypertension, as well as target organ damage.…”
mentioning
confidence: 99%
“…12,13 In addition, the currently used antihypertensive drugs are suggested to act on the central nervous system.…”
mentioning
confidence: 99%